Cacela revisited: a brief study of the architecture and landscape of Algarve, Portugal - Costa, Miguel Reimão (2014)
This article focuses on the integrated characterisation of Cacela, in the lower Algarve, by considering simultaneously the scales of landscape, urbanism and vernacular architecture. This analysis integrates a wider research and methodological approach, which combines analysing the cartographic and written sources, with the exhaustive surveying of the village and the recording of oral histories. It will be demonstrated that Cacela’s contemporary morphology results mostly from changes dating from the period between the end of the nineteenth century and the second quarter of the twentieth century. These changes were affected by the matrix of designs and structures from different periods of history, including the sixteenth century church and the village’s fortress.